Thermogravimetric Analysis and Kinetic Study on Catalytic Pyrolysis of Rice Husk Pellet using Its Ash as a Low-cost In-situ Catalyst - Wibowo, Wusana Agung; Cahyono, Rochim Bakti; Rochmadi, Rochmadi; Budiman, Arief (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
The thermogravimetric behaviors and the kinetic parameters of uncatalyzed and catalyzed pyrolysis processes of a mixture of powdered raw rice husk (RRH) and its ash (RHA) in the form of pellets were determined by thermogravimetric analysis at three different heating rates, i.e., 5, 10, and 20 K/min, from 303 to 873 K. This research aimed to prove that the rice husk ash has a catalytic effect on rice husk pyrolysis. To investigate the catalytic effect of RHA, rice husk pellets (RHP) with the weight ratio of RRH:ARH of 10:2 were used as the sample. Model-free methods, namely Friedman (FR), Kissinger-Akahira-Sunose (KAS), and Flynn-Wall-Ozawa (FWO), were used to calculate the apparent energy of activation(EA). The thermogravimetric analysis showed that the decomposition of RHP in a nitrogen atmosphere could be divided into three stages: drying stage (303-443 K), the rapid decomposition stage (443-703 K), and the slow decomposition stage (703-873 K). The weight loss percentages of each stage for both uncatalyzed and catalyzed pyrolysis of RHP were 2.4-5.7%, 35.5-59.4%, and 2.9-12.2%, respectively. Using the FR, FWO, and KAS methods, the values of Â for the degrees of conversion (a) of 0.1 to 0.65 were in the range of 168-256 kJ/mol for the uncatalyzed pyrolysis and 97-204 kJ/mol for the catalyzed one. We found that the catalyzed pyrolysis led the Â to have values lower than those got by the uncatalyzed one. This phenomenon might prove that RHA has a catalytic effect on RHP pyrolysis by lowering the energy of activation.